Activities carried out in the implementation of the Programme of Action for the Least Developed Countries for the decade 2011-2020 (UN New YorkUS, 2018)
Provides a description of activities carried out by UNCTAD, by pillar of work, between the second quarter of 2017 and the first quarter of 2018, as well as lessons learned and policy recommendations for the way forward.
Keywords: LEAST DEVELOPED COUNTRIES